Students in social vulnerability in distance education disciplines in times of COVID-19 (Research, Society and Development, 2020)
This work aims to analyze the social vulnerability of students in distance education disciplines in the time of COVID-19. It is a theoretical study of reflective analysis on the issues of social vulnerability faced by students in distance learning due to the need for social isolation. It is based on a review of narrative literature with discussion of the following points: Distance learning as a proposal due to social isolation and Distance Learning Students in social vulnerability. As a result, it is important to highlight the student's needs in terms of preparation to deal with information and communication technologies and, especially, those in situations of social vulnerability who do not have all the resources to access the content taught in the distance learning modality. An understanding of diversity, accessibility and the principles of inclusion must be taken into account so that the demands of students in situations of social vulnerability are isonically addressed.